2010
DOI: 10.1111/j.1540-8167.2010.01894.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Therapeutic INR on Activated Clotting Times, Heparin Dosage, and Bleeding Risk During Ablation of Atrial Fibrillation

Abstract: AF ablation with INR ≥ 2.0 provides a consistent anticoagulant milieu during the procedure, with lower heparin requirements that are important to anticipate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 15 publications
2
52
0
Order By: Relevance
“…Catheter ablation of AF under therapeutic INR is simple and requires smaller dose of intravenous heparin during the procedure [165].…”
Section: Thromboembolic Complications Preprocedural Thrombosis Tranmentioning
confidence: 99%
“…Catheter ablation of AF under therapeutic INR is simple and requires smaller dose of intravenous heparin during the procedure [165].…”
Section: Thromboembolic Complications Preprocedural Thrombosis Tranmentioning
confidence: 99%
“…In conducting ablation with ongoing warfarin, INR levels should be kept in the therapeutic range because a lower level of INR necessitates a larger amount of heparin during the procedure, which might lead to a higher risk of both bleeding and thrombosis. 16 …”
Section: Main Findingsmentioning
confidence: 99%
“…Several recent studies have shown that continued use of warfarin in the periprocedural period with therapeutic international normalized ratio (INR) is effective or better in preventing thromboembolic events in AF ablation procedures. 12- 16 The focus of these studies was incidence of thromboembolic events when warfarin was continued, compared to bridging with heparin and analogs, and did not assess whether continued warfarin resulted in an increased number of bleeding complications (BC) at the expense of fewer embolic events. We hypothesized that BC could increase with periprocedural therapeutic INR.…”
mentioning
confidence: 99%
“…In a study at the Brigham and Women's Hospital, we observed a 0.7% incidence of stroke or transient ischemic attack. 6 It is important to recognize that the incidence of asymptomatic embolic events may be much higher. In this issue of Circulation, Gaita et al 7 report a 0.4% incidence of clinically apparent stroke and a 14% incidence of silent cerebral embolism in 234 consecutive patients studied by cranial MRI the day after the ablation procedure.…”
Section: Article See P 1667mentioning
confidence: 99%